Issues of Modern Accounting of Intangible Assets (Eurasian Scientific Herald, 2023)
The article deals with the issues of modern accounting of intangible assets in accordance with national accounting standards and international financial reporting standards in Uzbekistan. A comparison was made between IAS- 38 and NAS-7 "Intangible Assets", discrepancies were identified and some measures were proposed to accelerate the introduction of international standards into national accounting practice.